2020
DOI: 10.1007/s10552-020-01282-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic factors for women with breast cancer in Malawi

Abstract: Background Breast cancer incidence in sub-Saharan Africa (SSA) is increasing, and SSA has the highest age-standardized breast cancer mortality rate worldwide. However, high-quality breast cancer data are limited in SSA. Materials and MethodsWe examined breast cancer patient and tumor characteristics among women in Lilongwe, Malawi and evaluated risk factor associations with patient outcomes. We consecutively enrolled 100 women ≥ 18 years with newly diagnosed, pathologically confirmed breast cancer into a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…In this cohort, among the 103 patients whose receptor status was known, majority were ER+or PR+accounting for about 68% of the cases, while 18(17%) had triple‐negative breast cancer (TNBC). Assuming these numbers to be representative of the broader cohort, this molecular breakdown is similar to other studies with patients of East and Southern African ancestry 32,36‐39 . However, hormone and HER‐2 receptor status was unknown in 71% of patients.…”
Section: Discussionsupporting
confidence: 77%
“…In this cohort, among the 103 patients whose receptor status was known, majority were ER+or PR+accounting for about 68% of the cases, while 18(17%) had triple‐negative breast cancer (TNBC). Assuming these numbers to be representative of the broader cohort, this molecular breakdown is similar to other studies with patients of East and Southern African ancestry 32,36‐39 . However, hormone and HER‐2 receptor status was unknown in 71% of patients.…”
Section: Discussionsupporting
confidence: 77%
“…Eighty-one were excluded after the title, abstract, and full-text review (Figure 1). Special requests sent to 4 authors yielded two additional articles (Benbakhtaet al, 2015;Rayne et al, 2019) while the other two could not be reached (Mody et al, 2013;Youngblood et al, 2020). Hand-searching and snow-balling yielded 21 more articles.…”
Section: Resultsmentioning
confidence: 99%
“…This is a common phenomenon in LIC where many factors have been reported that result in patients presenting with locally advanced disease as noted by recent studies from Malawi and Haiti. 6 , 27 A number of patients had ulcerated lesions, and none received RT to primary site for palliation of expected local symptoms from ulcerated breast lesion. Seven patients received palliative mastectomy in the RT group despite conflicting evidence on the role of surgery in the metastatic setting in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This is a common phenomenon in LIC where many factors have been reported that result in patients presenting with locally advanced disease as noted by recent studies from Malawi and Haiti. 6,27 A number of patients had ulcerated lesions, and none received RT to primary site for palliation of expected local symptoms from ulcerated breast lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation